2009
DOI: 10.1136/oem.2008.042432
|View full text |Cite
|
Sign up to set email alerts
|

Acute childhood leukaemia and residence next to petrol stations and automotive repair garages: the ESCALE study (SFCE)

Abstract: The results support the findings of our previous study and suggest that living next to a petrol station may be associated with acute childhood leukaemia. The results also suggest that the role of low-level exposure to benzene in acute childhood leukaemia deserves further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 30 publications
4
54
2
1
Order By: Relevance
“…The design of the ESCALE study of childhood leukemia has been reported elsewhere [20,[39][40][41][42][43][44]. The eligible AL cases were children diagnosed with AL in compliance with the registration criteria of the National Registry of Childhood Hematopoietic Malignancies (NRCH) between 1 January 2003 and 31 December 2004.…”
Section: Methodsmentioning
confidence: 99%
“…The design of the ESCALE study of childhood leukemia has been reported elsewhere [20,[39][40][41][42][43][44]. The eligible AL cases were children diagnosed with AL in compliance with the registration criteria of the National Registry of Childhood Hematopoietic Malignancies (NRCH) between 1 January 2003 and 31 December 2004.…”
Section: Methodsmentioning
confidence: 99%
“…The negative effects of petrol vapour exposure on the health among petrol station attendants and residents in the vicinity of petrol stations have also been studied. It has been reported that exposure to petrol vapour increases the risk of acute myeloid leukaemia (Jakobsson et al, 1993), acute childhood leukaemia (Brosselin et al, 2009;Steffen et al, 2004), prostate cancer (Seidler et al, 1998) and other forms of cancer at various parts of the body (Lagorios et al, 1994). Artificial Neural Networks were also used to predict benzene exposure patterns for filling station employees (Sarigiannis et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Les études portant sur le rôle du trafic automobile et des polluants benzéniques, bien qu'encore peu nombreuses, suggè-rent que la proximité immédiate de routes à gros trafic pourrait augmenter le risque de leucémie de l'enfant [2]. S'en rapprochent les résultats de deux études castémoins successives réalisées par l'unité Inserm 1018 évoquant l'augmentation du risque de leucémie à proximité immédiate de garages ou de stations-service [6,28]. L'influence du trafic automobile sur le risque de tumeur cérébrale a été moins étudiée et les données sont inconsistantes [17].…”
Section: Hydrocarburesunclassified